2021
DOI: 10.1093/ajcn/nqaa327
|View full text |Cite
|
Sign up to set email alerts
|

Infections and systemic inflammation are associated with lower plasma concentration of insulin-like growth factor I among Malawian children

Abstract: Background Insulin-like growth factor I (IGF-I) is the most important hormonal promoter of linear growth in infants and young children. Objectives The objectives of this study were to compare plasma IGF-I concentration in a low- compared with a high-income country and characterize biological pathways leading to reduced IGF-I concentration in children in a low-income setting. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…This statement is supported by a Kenyan study with HIV-positive SAM children responding to feeding therapy, which showed an average height increase of 0.34 mm/day over 60 days of follow-up, but demonstrated a negative correlation between the systemic inflammatory markers IL-2, IL-17a, and LBP with their growth (Njunge et al, 2020). Additionally, Maleta K. et al reported, in 2021, a comparison between 716 Malawian and 80 Finnish children and found that at 18 months old, Malawian children had almost half the concentration of IGF-1 of that found in Finns (Maleta et al, 2021). They also reported a strong relationship of low plasmatic IGF-1 levels with the systemic inflammatory marker CRP in a dose-dependent way, and with intestinal infection by Campylobacter or Shigella bacteria (Maleta et al, 2021).…”
Section: Biomarkers Of the Severity Of Inflammation In Severe Acute M...mentioning
confidence: 99%
See 1 more Smart Citation
“…This statement is supported by a Kenyan study with HIV-positive SAM children responding to feeding therapy, which showed an average height increase of 0.34 mm/day over 60 days of follow-up, but demonstrated a negative correlation between the systemic inflammatory markers IL-2, IL-17a, and LBP with their growth (Njunge et al, 2020). Additionally, Maleta K. et al reported, in 2021, a comparison between 716 Malawian and 80 Finnish children and found that at 18 months old, Malawian children had almost half the concentration of IGF-1 of that found in Finns (Maleta et al, 2021). They also reported a strong relationship of low plasmatic IGF-1 levels with the systemic inflammatory marker CRP in a dose-dependent way, and with intestinal infection by Campylobacter or Shigella bacteria (Maleta et al, 2021).…”
Section: Biomarkers Of the Severity Of Inflammation In Severe Acute M...mentioning
confidence: 99%
“…Additionally, Maleta K. et al reported, in 2021, a comparison between 716 Malawian and 80 Finnish children and found that at 18 months old, Malawian children had almost half the concentration of IGF-1 of that found in Finns (Maleta et al, 2021). They also reported a strong relationship of low plasmatic IGF-1 levels with the systemic inflammatory marker CRP in a dose-dependent way, and with intestinal infection by Campylobacter or Shigella bacteria (Maleta et al, 2021). Despite the fact that it has not been clinically evaluated in SAM children, an experimental work performed in dogs inoculated with E. coli-derived LPS has shown an important decrease in IGF-1 levels, as well as in the anti-diabetic hormone adiponectin (Tvarijonaviciute et al, 2011), suggesting that infection with this bacterium potentially could limit growth while promoting diabetes in affected children.…”
Section: Biomarkers Of the Severity Of Inflammation In Severe Acute M...mentioning
confidence: 99%
“…We chose this age interval as it is a period when infections are common (Fan et al, 2019;MAL-ED Network Investigators, 2017;Platts-Mills et al, 2015) and growth faltering still continues (Espo et al, 2002;Maleta et al, 2020;Victora et al, 2010) among children in low-income countries.…”
Section: Study Design and Concept Mapmentioning
confidence: 99%
“…One such exposure is systemic inflammation, which can block IGF‐1 synthesis in the liver (Walters & Griffiths, 2009 ). Inflammation is often caused by infections, and both symptomatic and asymptomatic infections have been associated with reduced plasma concentrations of IGF‐1 among infants and young children in low‐income settings (DeBoer et al, 2017 ; Maleta et al, 2020 ; Prendergast et al, 2014 ; Syed et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in chronic inflammatory conditions, such as experimental arthritis, plasma concentrations of IGF-1 and GH as well as pituitary GH mRNA are decreased [2,7,8]. In children with cystic fibrosis, juvenile idiopathic arthritis, or inflammatory bowel diseases, an alteration in both GH and IGF-1 secretion has also been observed, together with growth retardation [9,10]. Furthermore, critically ill patients during the acute phase of the illness have an increase in GH with a decrease in IGF-1 and in the main plasma IGF-1 binding protein-3 (IGFBP-3).…”
Section: The Hypothalamic-gh-igf-1 Axis In Inflammationmentioning
confidence: 99%